Self-regulatory processes in goal striving during excellent distance-running performances: A qualitative study - Jackman, P. C.; Whitehead, A. E.; Swann, C.; Brick, N. E. (Psychology of Sport and Exercise, 2024)
Objective Goal setting can improve endurance performance, yet how endurance performers maintain goal striving and bring it to a successful close has received limited attention. In this study, we investigated the self-regulatory processes employed by long-distance runners during goal striving in excellent competitive performances.